Medical and Pharmacy Students’ Perceptions Regarding Generic Medicines in Yemen - Al-mohamadi, Ahmed; M. Halboup, Abdulsalam; Mohamed Ibrahim, Mohamed Izham; Abdulghani, Mahfoudh; Al-Woraf, Yaser Mohammed; Otham, Gamil; Alshakka, Mohammed; Ansari, Mukhtar (Journal of Pharmacy Practice and Community Medicine)
Objective: The study is to evaluate Yemeni medical and pharmacy students’ knowledge and attitude regarding generic medicines. Method: A cross-sectional survey was used to collect data from final-year medical and pharmacy students at six public and private universities in Yemen. The questionnaire was distributed among the students through their course coordinators. Students were clearly informed about the objective of the study and their written consents were taken before the survey. The responses were entered in SPSS, and descriptive and inferential analyses were carried out. Results: The response rate was 60.1%. Overall the half of participants’ perception regarding generic medicine was positive. Perceptions of pharmacy students’ regarding generic medicines were better than those of the medical students. Conclusion: The present study concluded that both studied groups had insufficient knowledge about quality, safety and bioequivalence of generic medicines. The medical students showed poorer knowledge than pharmacy students which need to give more attention from educators regarding the use of generic medicines.
Keywords: Generic drugs; Medical students; Perception; Pharmacy students; Yemen